Beyond the Ward: Strategic Insights into Enhancing Healthcare Professionals Performance Through Organizational Environment and Individual Values Synergy - Nurhasanah, Neneng; Suseno, Bambang Dwi; Basrowi, Basrowi; Maskudi, Maskudi (Universitas Padjadjaran, 2024)
This research aims to explore how various factors within the organizational context influence the affective commitment and performance of Non-State Civil Apparatus (SCS) Health Workers in Government Hospitals in Serang Regency and City. It specifically investigates the direct effects of organizational environment and individual values on both affective commitment and performance of health workers, employing a quantitative, correlational approach to analyze these relationships. The study involves 531 Non-ASN Health Workers, with a sample size of 170, using survey methods for data collection. A key objective is to examine affective commitment's role as a mediator in the relationship between organizational context and worker performance. This study offers significant insights into how the interplay between organizational environment, individual values, and affective commitment influences health workers' performance, contributing to the broader understanding of healthcare professional dynamics in government hospitals.